The right to roam. From UK to WA? - Hughes, Michael; Tye, M. (Parks and Leisure Australia WA, 2010)
This paper presents an international review of policy and management regarding public recreational access to land of varying tenure and how it relates to Western Australia. This is an increasingly important issue in Australia with a growing population and associated pressure on natural resources to provide a range of services and needs. Government has identified a need to clearly define ‘access’ and better understand the complex legislative and non-legislative determinants governing access to land in Australia. The project defined responsible outdoor recreation access as individual or group walking based activities centred on responsible interaction within natural environments. Policy, legislation and management of recreational walking access to land, referred to as the right to roam, in the UK and New Zealand were reviewed. A comparative review of policy, legislation and management of land in WA was then conducted with regard to how this influences public access to land for walking based recreation. A significant portion of land in the UK and NZ is privately owned freehold that functioned to restrict public access to natural areas for recreation. It was found that establishment of a right to roam in the UK and NZ was based on several key elements: a clear justification for the right to roam, strong and broad community support, protection of landholder’s rights, and a consistent approach to implementation and management of the right to roam.In contrast, land in WA is primarily publically owned (93%). Public recreational access is determined more by the sometimes multiple management overlays that exist in any given area. As a consequence, the status of land accessibility in WA can be fluid and complex owing to the multiple management regimes and policies that can apply to any given area and adjustments in policy and management that can occur over time. This creates uncertainty with regard to rights of recreational access in WA. Understanding policy and management in regions where the right to roam has been established and how this relates to WA can inform a more strategic approach to public access to land in Australia.